Curriculum Management in Improving Education Quality at SMAN 1 and SMAN 11 Banda Aceh - Midriani, Noni; Murniati, Murniati; Bahrun, Bahrun (Jurnal Pendidikan Progresif, 2021)
The aim of this research is to determine the planning, implementation, evaluation, and curriculum barrier in improving the eductaion quality at SMAN 1 and SMAN 11 Banda Aceh. The research method used in this research is descriptive method with qualitative approach. The technique of data collection used are observation, interview, and documentation study. The respondents were the principals, vice principals, school development team, teachers, and supervisors. The result shows that: (1) the curriculum development began with the school academic calender, extracurriculer activities, and teaching duty arrangement; (2) The curriculum implementaion relies on the planning which has been decided; (3) Curriculum evaluation which is implemented by the principals and teachers runs well. and (4) The barrier in implementing the curriculum is that the curriculum program its self has not been implemented yet as what it is expected both by the principal and the teacher. Keywords: curriculum management, education quality, Banda Aceh DOI: http://dx.doi.org/10.23960/jpp.v11.i2.202101